Peranan Komunikasi dalam Kepemimpinan Organisasi di Dinas Kebudayaan Pariwisata Pemuda dan Olahraga Kota Sibolga - Rosita Megawati Lumbangtobing (FLOW, 2013)
“The role of communication in organizational leadership” is the title of this thesis, subbed with “Descriptive study of the role of communication in organizational leadership at Sibolga Agency of Culture Tourism Youth and Sporst” It aims at finding out the role of communication in organizational leadership at Sibolga Agency of Culture Tourism Youth and Sporst. This research applies descriptive-qualitative method, i.e. a type of research to describe phenomenons, facts or happenings systematically and accurately of the research and to analyze the truth as well based on the obtained data. Data collection is worked through interview and observation which are the materials for analysis using interpretation. Six government officials, who are posted structural heads of The Sibolga Agency of Culture Tourism Youth and Sporst, are the informants of this research. Sampling technique is purposive sampling, placing the Head of the Agency as the key informant and five other officials as common informants –Secretary and four Division Heads. Through descriptive analysis, thirteen themes are gained as the result of the communication role in organizational leadership at Sibolga Agency of Culture Tourism Youth and Sporst. They are : (1) Arousing Understanding, (2) Giving Pleasure, (3) Changing Attitude, (4) Managing the Harmony, (5) Producing Action, (6) Trusting Each other, (7) Teamwork Spirit, (8) Respecting Status and Role, (9) Human Resources Optimalization, (10) Time Efficiency, (11) Motivating, (12) Bureucracy, and (13) Problem Solving. The research shows that communication plays a significant role in organizational leadership, and it can be concluded that the role of communication in organizational leadership at Sibolga Agency of Culture Tourism Youth and Sporst runs effectively in the same line with the five effective communication indicators (Suranto AW 2005 : 105) i.e. : (1) Understanding, (2) Pleasure, (3) Behavioural Changing, (4) relationship, and (5) (Action).